2013
DOI: 10.1074/jbc.m112.423954
|View full text |Cite
|
Sign up to set email alerts
|

An N-terminal Fragment of the Prion Protein Binds to Amyloid-β Oligomers and Inhibits Their Neurotoxicity in Vivo

Abstract: Background: The cellular prion protein (PrPC) could be a toxicity-transducing receptor for amyloid-β (Aβ) oligomers.Results: N1, a naturally occurring fragment of PrPC, binds Aβ oligomers, inhibits their polymerization into fibrils, and suppresses their neurotoxic effects in vitro and in vivo.Conclusion: N1 binds tightly to Aβ oligomers and blocks their neurotoxicity.Significance: Administration of exogenous N1 or related peptides may represent an effective therapy for Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
199
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(223 citation statements)
references
References 34 publications
20
199
4
Order By: Relevance
“…When the levels of PrP-interacting A␤ rise as a function of age and eventually hit a critical value, mice demonstrate escalating cognitive decline. Interestingly, the threshold amount of PrP C -interacting A␤o lies close to reported affinity of PrP C toward the A␤ oligomer (K D was determined to be in the low nanomolar range), which could explain why lower concentrations of PLISA-detectable A␤o have little effect on cognitive performance (22,28). The rates of A␤ oligomer accumulation varied dramatically between transgenic AD model mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the levels of PrP-interacting A␤ rise as a function of age and eventually hit a critical value, mice demonstrate escalating cognitive decline. Interestingly, the threshold amount of PrP C -interacting A␤o lies close to reported affinity of PrP C toward the A␤ oligomer (K D was determined to be in the low nanomolar range), which could explain why lower concentrations of PLISA-detectable A␤o have little effect on cognitive performance (22,28). The rates of A␤ oligomer accumulation varied dramatically between transgenic AD model mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between A␤o and PrP C is essential for development of an array of AD features, including activation of certain signaling cascades, synaptotoxicity, inhibition of long term potentiation, memory impairment, and decreased survival in mice (25,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). However, it was also observed that A␤o can induce AD-like phenotypes independently of PrP C in J20 mice (44) and in some in vitro studies (23,24,45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic N1 fragment, equivalent of that released by α-cleavage of endogenous PrP C , has been found to bind Aβ oligomers with high affinity, sequester Aβ oligomers in the extracellular space, and hence block the Aβ oligomer-mediated synaptic toxicity (82). Therefore, exogenous administration of N1 or enhancement of endogenous α-cleavage of PrP C represents a brand-new class of therapeutic approaches for AD.…”
Section: Prpmentioning
confidence: 99%
“…N1 binds to Aβ oligomers with high affinity, and blocks the neurotoxicity of Aβ oligomers through neutralizing toxic assemblies of Aβ. Therefore, N1 may serve as a potent inhibitor of Aβ oligomer toxicity and represent an entirely new class of therapeutic agents for the treatment of AD (82). N1 is a naturally occurring soluble fragment that is generated by endogenous proteolytic processing of PrP C at the α-site (residues 111 and 112) (83), presumably by ADAM (a disintegrin and metalloprotease) proteases (84)(85)(86)(87).…”
Section: Prpmentioning
confidence: 99%